Planning Of A Public Library In Medan City With The Application Of A Natural Ventilation System - Desy Lukita Silky; Bhakti Alamsyah; Ramadani Fitri (INFOKUM, 2022)
Some construction projects, if they are not managed properly, can produce large amounts of waste and energy, so construction project management is needed with the application of an environment-based natural ventilation system. Construction of a public library building in the city of Medan in this problem there is a need for research to identify green mode in building construction planning. The method used in this study. From the results of this study, it was found that the Appropriate Aspects of Land Use reached 86.3%. Aspects of Health and Comfort in the project environment reached 69.4%, Aspects of building environmental management reached 33.3%, Aspects of Source and Material Cycle reached 73.3%, Aspects of conservation and energy efficiency reached 25% and Aspects of water conservation reached 30%. Judging from the indicators fulfilled, namely reaching more than 50%, the aspects that meet the green construction criteria in the central library building are the Appropriate Land Use Aspects, Health and Comfort Aspects in the Project Environment and Sources, and Material Cycle Aspects. Therefore, from the identification, the total achievement of green construction indicators in the construction of the Tanjungpura University Library Building is 53.52%.